Socioeconomic Impacts of Digitisation in Saudi Arabia - Neffati, Mohamed; Gouidar, Abdessalem (International Journal of Economics and Financial Issues, 2019)
The aim of this paper is to measure and analyse the socioeconomic effects of digitisation in Saudi Arabia by using data for the period 1981–2016. Adopting the autoregressive distributed lag and the fully modified least squares approaches, the results reveal significant relationships between the digitisation and socioeconomic variables. Notably, digitisation contributes to the gross domestic product, reduces unemployment, and enhances transparency. Thus, digitisation can be considered a new impetus growth and a powerful instrument of economic diversification that permits the transition to a knowledge-based economy. Keywords: Digitisation, socioeconomic, transparency JEL Classifications : J24, O3, O47, O5 DOI: https://doi.org/10.32479/ijefi.7718